2007
DOI: 10.1111/j.1551-2916.2007.01933.x
|View full text |Cite
|
Sign up to set email alerts
|

New Family of Dielectric Materials in Ca–Y–Ti–Nb–O System Having Pyrochlore Type Structure

Abstract: A new family of pyrochlore-type oxides in the Ca-Y-Ti-Nb-O system has been prepared by the conventional solid-state route. These compounds have a dielectric constant (K) in the range 27-92 and, further, the dielectric properties are found to be independent of frequency in the 100 Hz to 1 MHz range for all the compositions in the temperature range 301-1001C. Their temperature coefficient of the dielectric constant is negative and in the range À80 to À612 ppm/1C. Rietveld analysis of the X-ray diffraction data e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Recently, the authors have reported a new family of dielectric materials in Ca-Y-Ti-Nb-O system for their dielectric properties. 14,15 The continuing drive to discover new materials with better dielectric properties suggests that the evaluation of new dielectric materials should be a fruitful area of research. In the present study, a series of pyrochlore type oxides with the chemical formula, PbRETiTaO 7 (RE5Y, La, Nd, Sm, Gd, or Dy) have been prepared which show somewhat low variation of dielectric properties in the temperature range 30-100uC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors have reported a new family of dielectric materials in Ca-Y-Ti-Nb-O system for their dielectric properties. 14,15 The continuing drive to discover new materials with better dielectric properties suggests that the evaluation of new dielectric materials should be a fruitful area of research. In the present study, a series of pyrochlore type oxides with the chemical formula, PbRETiTaO 7 (RE5Y, La, Nd, Sm, Gd, or Dy) have been prepared which show somewhat low variation of dielectric properties in the temperature range 30-100uC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported pyrochlore based dielectric materials in Ca-Y-Ti-Nb-O system having dielectric constant ͑K͒ in the range of 27-92. 15 During the present study, we could prepare some solid solutions of niobates and tantalates in Ca-RE-Ti-M -O ͑RE=Sm or Dy and M =Nb or Ta͒ system, which also have pyrochlore-type structure and some of these solid solutions show only very small variation in dielectric constant when the temperature is varied from −50 to 100°C. The structure and dielectric properties of these materials and their variation with composition and temperature were investigated some what in detail and the results are presented in this paper.…”
mentioning
confidence: 99%